2014
DOI: 10.1007/s00430-014-0343-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nystatin A1 derivatives exhibiting low host cell toxicity and antifungal activity in an in vitro model of oral candidosis

Abstract: Opportunistic oral infections caused by Candida albicans are frequent problems in immunocompromised patients. Management of such infections is limited due to the low number of antifungal drugs available, their relatively high toxicity and the emergence of antifungal resistance. Given these issues, our investigations have focused on novel derivatives of the antifungal antibiotic Nystatin A1, generated by modifications at the amino group of this molecule. The aims of this study were to evaluate the antifungal ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
(83 reference statements)
0
13
0
1
Order By: Relevance
“…; Boros‐Majewska et al . ), which revealed that as OligoG was not fungicidal (as ascertained by the absence of red‐stained, non‐vital cells), differential quantification of samples, as previously described by Boros‐Majewska et al . (), could not be employed.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…; Boros‐Majewska et al . ), which revealed that as OligoG was not fungicidal (as ascertained by the absence of red‐stained, non‐vital cells), differential quantification of samples, as previously described by Boros‐Majewska et al . (), could not be employed.…”
Section: Discussionmentioning
confidence: 62%
“…), which revealed that as OligoG was not fungicidal (as ascertained by the absence of red‐stained, non‐vital cells), differential quantification of samples, as previously described by Boros‐Majewska et al . (), could not be employed. Analysis of invasion in the RHE and agar models revealed that while no differences in fungal viability were evident, OligoG treatment induced markedly reduced invasion in both model systems, with a dose‐dependent decrease in hyphal formation being evident in the agar model.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In addition, some of synthetic antifungals are potentially toxic for the host cells due to the similarity in both eukaryotic fungal and human cell components, such as sterols (Berman & Sudbery 2002). Biochemical engineering has been used to modify standard antifungals or even develop novel lowtoxicity drugs (Boros-Majewska et al 2014;Peng et al 2015), but most drugs have not been tested in humans. Taken together, all these aspects have encouraged an active search for novel candidates to manage oral candidiasis in susceptible patients.…”
Section: Introductionmentioning
confidence: 99%
“…多烯大环内酯抗生素的溶血毒性 [56] , 尤其是C3′位氨 基的二(氨基丙烷基)衍生(如两性霉素B衍生物28, 图 4)可以使衍生物的抗真菌活性提高10倍以上, 而溶 血毒性下降2.5倍左右(表1) [32] . 环外羧基衍生与C3′ 位氨基衍生相结合, 能够进一步提高多烯大环内酯 衍生物的抗真菌活性, 并降低其溶血毒性 [57] .…”
Section: 氨基海藻糖C3′位氨基的化学衍生往往能够有效降低unclassified